Bethlehem's Syriac Christians : Self, nation and church in dialogue and practice - Calder, Mark (The Modern Muslim World, 2017)
An anthropological study of Syriac Orthodox Christian identity in a time of displacement, upheaval, and conflict. For some Syriac Orthodox Christians in Bethlehem, their self-articulation - the means by which they connect themselves to others, things, places and symbols - is decisively influenced by their eucharistic ritual. This ritual connects being siryāni to a redeemed community or 'body', and derives its identity in large part from the Incarnation of God as an Aramaic-speaking Bethlehemite.